Pembuatan Website Katalog Produk Pada Toko Atlanta (Information Technology and Telematics, 2015)
Abstrak This study examines design in the product catalog. The problem is how to create a catalog view that could make the user comfortable in accessing the catalog. The study produced a display that is responsive to the catalog katolg Atlanta Stores Electronics. With these catalogs can be used for media recognition of electronic products to customers. Through this catalog, we hope Store Atlanta can gain more customers. To repair the fore, enhance the appearance and adding online ordering menu into the next plan. Keyword : Katalog, PHP, MySQL